Genetic approaches to the development of novel designs for population control of two vector mosquitoes: Aedes aegypti and Culex quinquefasciatus. - Flis, I (2017)
The prevention or reduction of infectious pathogen transmission is essential for safeguarding human health and species conservation, and can be achieved through vector control. New genetics-based innovations have proven to be a viable solution for the successful suppression or eradication of insect vectors, whilst also providing opportunities for further improvements and enhancements. In this thesis, I examine a vector control approach incorporating genetically engineered late-acting lethality, and investigate the character and function of the genetic elements that could lead to improvement of this approach. I start by assessing the functionality of the late-acting, doxycycline-repressible lethal system in transgenic Aedes aegypti. I find that the induced lethality is specific to the late developmental stage and occurs in the vast majority of the individuals carrying the lethal transgene. I also show that the induced phenotype is strongly repressible in the presence of the antidote, which is a crucial prerequisite of a practical RIDL (Release of Insect carrying Dominant Lethal gene) system. Next, I investigate the Culex quinquefasciatus Actin-4 gene and its potential use to induce a flightless phenotype. I find that the expression of the Actin-4 is sex-specific and, by generating a novel mutant via gene editing, that the gene is haploinsufficient or dominant negative in inducing the flightless phenotype in females. Additionally, I provide further support for the effectiveness of the recently discovered CRISPR/Cas9 system by showing that it successfully induces targeted editing of the Actin-4 gene. My findings provide novel genetic tools for the development of various genetics-based strategies for control of invasive vector mosquitoes.